2018
DOI: 10.1093/dnares/dsy039
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of the non-conventional wine yeastHanseniaspora guilliermondiiUTAD222 unveils relevant traits of this species and of theHanseniasporagenus in the context of wine fermentation

Abstract: Hanseanispora species, including H. guilliermondii, are long known to be abundant in wine grape-musts and to play a critical role in vinification by modulating, among other aspects, the wine sensory profile. Despite this, the genetics and physiology of Hanseniaspora species remains poorly understood. The first genomic sequence of a H. guilliermondii strain (UTAD222) and the discussion of its potential significance are presented in this work. Metabolic reconstruction revealed that H. guilliermondii is not equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 90 publications
3
39
0
Order By: Relevance
“…Among these yeasts, the genus Hanseniaspora, which can play a critical role in the modulation of the wine sensory profile by increasing its complexity and organoleptic richness, is attracting a significant interest (Fleet, 2003). So far, the knowledge on genetics and physiology of Hanseniaspora species remains limited, notwithstanding some recent significant studies open new perspectives in the field, revealing speciesspecific properties to be explored (Langenberg et al, 2017;Seixas et al, 2019). In this context, genomics analysis may enable a correlation between genetics and useful traits, which could provide a roadmap for biotechnological exploitations (Hittinger et al, 2015;Riley et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Among these yeasts, the genus Hanseniaspora, which can play a critical role in the modulation of the wine sensory profile by increasing its complexity and organoleptic richness, is attracting a significant interest (Fleet, 2003). So far, the knowledge on genetics and physiology of Hanseniaspora species remains limited, notwithstanding some recent significant studies open new perspectives in the field, revealing speciesspecific properties to be explored (Langenberg et al, 2017;Seixas et al, 2019). In this context, genomics analysis may enable a correlation between genetics and useful traits, which could provide a roadmap for biotechnological exploitations (Hittinger et al, 2015;Riley et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For S. cerevisiae, the assimilation of preferred nitrogen sources can be explained mainly by the regulation of nitrogen transport, including the Ssy1p-Ptr3p-Ssy5 (SPS) system [53] and the nitrogen catabolism repression (NCR) system [43,54]. These mechanisms have been scarcely explored in NS wine yeasts, as only recent studies had been done in the Hanseniaspora genus [52,55]. In fact, Lleixa et al [52] demonstrated that the NCR mechanism could also be present in some NS species, specifically in H. vineae [52].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Lleixa et al [52] demonstrated that the NCR mechanism could also be present in some NS species, specifically in H. vineae [52]. However, Seixas et al [55] evidenced that almost all S. cerevisiae amino acid-specific permeases were absent in Hanseniaspora guilliermondii, Hanseniaspora opuntiae, or H. uvarum, suggesting that Hanseniaspora species might favor the utilization of general nitrogen permeases instead of specific ones. Another recent study performed in Kluyveromyces marxianus [37] evidenced that the nitrogen regulation in this species was dissimilar to the one in S. cerevisiae, lacking some key ammonium permeases, such as Mep1 and Mep2.…”
Section: Discussionmentioning
confidence: 99%
“…Seixas et al [99] reported the reconstruction of the metabolic network for H. guilliermondii UTAD222, noting that this strain of yeast contains four genes that code for β-glucosidases, as well as the genes necessary for the synthesis of acetaldehyde, ethyl esters and higher alcohols. Surprisingly, no S. cerevisiae acetyl transferase-like proteins, involved in the synthesis of acetate esters, were found in the ORFeome of H. guilliermondii UTAD222.…”
Section: Hanseniasporamentioning
confidence: 99%